PENGARUH KUALITAS PRODUK MINUMAN KOPI TERHADAP KEPUASAN KONSUMEN DI RIMBUN KOPI BATAM - Hastuti Rebeca Talaksoru; Maldin, Siska Amelia (Puslitabmas Batam Tourism Polytecnic, 2023)
Consumer goals are a person's feelings of pleasure or disappointment that arise after the expected performance (result). Consumer satisfaction can be said to be achieved if the results are of good quality. This research was conducted at Rimbun Kopi Batam, which is located on Jl. Raja H.Fisabilillah No.7, Tlk. Tering, district. Batam City, Batam City. This study aims to determine the effect of the quality of coffee beverage products on consumer satisfaction at Rimbun Kopi Batam. The type of research used is quantitative research with associative method using simple linear regression with SPSS 26.0 progress. The sample of this research is 99 respondents who are consumers in Rimbun Kopi Batam. The sampling technique used accidental sampling technique. The data collection method used in this research is by distributing questionnaires. From the t test that has been done it can be concluded that there is a relationship between the variables of product quality to partial consumer satisfaction, namely with a ratio of thitung values greater than ttabel which is 4,137> 1,984. These results showed that the quality of the products studied in the study contributed 15% to explaining the changes in consumer satisfaction, the remaining 85% was affected by other variables not analyzed in the study model